Performatividade em rede e inteligência coletiva no YouTube - Cavalcante, Laíse Barbosa (2021)
The communicational processes in the network establish a social performative context with several consequences, among them, reverberations in the learning mechanisms. This is because the technological innovations, especially those of communication and information, affect the forms of sociability, languages and cognition, arising new ways of act. This dissertation analyzes a performative behavior that emerges today, that is the consumption of instructional and educational content, from short videos to carry out a project. For this, we checked the records of the interactions taken on four channels of the YouTube video sharing platform, named: Manual do Mundo, Paloma Cipriano, Professor Noslen and Algodão Cru. Through the phenomenological approach, we identified that this behavior is collaborative, reviews issues of time and place to learn, has applicability in the daily lives of individuals and results in new social performances that, among other things, echo in the identification of users with formal models or in person teaching. We demonstrate that this behavior adheres to concepts of learning, with articulation with the interactionist strand and that these informal and non-formal ways of learning through interactive media, go beyond educational objectives applied in formal education. We highlight the performative materiality of social media in the communicative processes established in it and how these processes continuously impact the actors who participate in them. Finally, we reflect on the recent expansion of this behavior, the need to learn networked, collaboratively, in the very exercise of sociability, as shown by the reality in the face of the Covid-19 pandemic.